Efficacy, safety and response predictors of adjuvant astragalus for diabetic kidney disease (READY): study protocol of an add-on, assessor-blind, parallel, pragmatic randomised controlled trial - Kathryn Choon Beng Tan; Lixing Lao; Yanbo Zhang; Kam Wa Chan; Alfred Siu Kei Kwong; Pun Nang Tsui; Simon Chi Yuen Cheung; Gary Chi Wang Chan; Wing Fai Choi; Wai Han Yiu; Michelle Man-Ying Wong; Zhang-Jin Zhang; et al. (BMJ Open)
Introduction Diabetic kidney disease (DKD) is a prevalent and costly complication of diabetes with limited therapeutic options, being the leading cause of end-stage kidney disease in most developed regions. Recent big data studies showed that add-on Chinese medicine (CM) led to a reduced risk of end-stage kidney disease and mortality among patients with chronic kidney disease (CKD) and diabetes. Astragalus, commonly known as huang-qi, is the most prescribed CM or used dietary herb in China for diabetes and DKD. In vivo and in vitro studies showed that astragalus ameliorated podocyte apoptosis, foot process effacement, mesangial expansion, glomerulosclerosis and interstitial fibrosis. Nevertheless, the clinical effect of astragalus remains uncharacterised. This pragmatic clinical trial aims to evaluate the effectiveness of add-on astragalus in patients with type 2 diabetes, stage 2–3 CKD and macroalbuminuria, and to identify related response predictors.Methods and analysis This is an add-on, assessor-blind, parallel, pragmatic randomised controlled clinical trial. 118 patients diagnosed with DKD will be recruited and randomised 1:1 to receive 48 weeks of add-on astragalus or standard medical care. Primary endpoints are the changes in estimated glomerular filtration rate and urine albumin-to-creatinine ratio between baseline and treatment endpoint. Secondary endpoints include adverse events, fasting blood glucose, glycated haemoglobin, lipids and other biomarkers. Adverse events are monitored through self-complete questionnaire and clinical visits. Outcomes will be analysed by regression models. Subgroup and sensitivity analyses will be conducted for different epidemiological subgroups and statistical analyses. Enrolment started in July 2018.Ethics and dissemination This study was approved by the Institutional Review Board of the University of Hong Kong/Hospital Authority Hong Kong West/East/Kowloon Central clusters (UW 16-553/HKEC-2019-026/REC (KC/KE)-19-0049/ER-4). We will report the findings in medical journals and conferences. The dataset will be available on reasonable request.Trial registration number NCT03535935